Effect of feeding enzyme mixture with Fibrolytic activity in dry and solubulized Forms on the performance of lambs - M.V.A.N. Suryanarayana; J. V. Ramana (Indian Journal of Veterinary and Animal Sciences Research, 2025)
One hundred lambs (11.8 kg ± 0.56) divided at random into 4 groups G1, G2, G3 and G4 were supplemented with exogenous fibrolytic enzyme mixture (EFE) in concentrates after 6 hours outside grazing. G1 and G2 were given 200 and 400 g of EFE per 50 kg feed in dry form, G3 and G4 were given EFE in solubulized form at 20 and 40 g per litre of water, respectively. The initial and final weights (kg) were non-significant among treatments. The total weight gain (kg) was higher (P<0.05) for G4 and G2 as compared to other two. Average daily gain (g) was highest (P<0.05) for G4 followed by G2, G1 and G3. Total weight gain (%) is 15, 7.6 and 16.5 lower (P<0.05) for G1, G2 and G3 (Table) as compared to G4. Lowest (P<0.05) FCR was observed for G4 and is in the order of G4< G2< G1< G3. The cost of the feed per kg gain was lower (P<0.05) by 21%, 26% and 13% for G4 as compared to G1, G2 and G3. It can be concluded that addition of EFE in solubulized form was found better for the reason that it forms a stable complex with the feed and thus facilitates for the rumen bacterial attachment earlier for rapid action due to an increase in rumen bacterial population